The Effect of Relationship Marketing on Customer Loyalty: A Case Study - Ansori, Putra Budi (Adpebi International Journal of Multidisciplinary Sciences, 2022)
This research was conducted at PT.Hasel Milek Jaya Pekanbaru in 2022. The purpose of this study was to determine the effect of relationship marketing on customer loyalty at PT.Hasel Milek Jaya. The population in this study were all customers in 2021 as many as 727 customers. Thus the number of samples is rounded up to 88 consumers, after being calculated by the Taro Yamane formula. The sampling technique was carried out by purposive sampling. Based on the results of the hypothesis test, the calculated t value is 10.832 > the t table value is 1.98793, then H0 is rejected and Ha is accepted. It means that Relationship Marketing has a significant effect on Customer Loyalty at PT. Hasel Milek Jaya. Or the hypothesis has a significant effect because the value of Sig < 0.05. It was found that Relationship Marketing contributed to changes in the Customer Loyalty variable by 57.7%, while the remaining 42.3%. (100%-57.7%) influenced by other variables not examined in this study